Lattice dynamics of BaFe2Se3. (23rd June 2022) - Weseloh, M J; Balédent, V; Zheng, W; Verseils, M; Roy, P; Brubach, J B; Colson, D; Forget, A; Foury-Leylekian, P; Lepetit, M-B
Abstract: This paper presents a study of the lattice dynamics in BaFe2 Se3 . We combined first-principle calculations, infrared measurements and a thorough symmetry analysis. Our study confirms that Pnma cannot be the space group of BaFe2 Se3, even at room temperature. The phonons assignment requires Pm to be the BaFe2 Se3 space group, not only in the magnetic phase, but also in the paramagnetic phase at room temperature. This is due to a strong coupling between a short-range spin-order along the ladders, and the lattice degrees of freedom associated with the Fe–Fe bond length. This coupling induces a change in the bond-length pattern from an alternated trapezoidal one (as in Pnma ) to an alternated small/large rectangular one. Out of the two patterns, only the latter is fully compatible with the observed block-type magnetic structure. Finally, we propose a complete symmetry analysis of the BaFe2 Se3 phase diagram in the 0–600 K range.